2008
DOI: 10.1016/j.neuron.2008.09.035
|View full text |Cite
|
Sign up to set email alerts
|

The Globus Pallidus Sends Reward-Related Signals to the Lateral Habenula

Abstract: Summary As a major output station of the basal ganglia, the globus pallidus internal segment (GPi) projects to the thalamus and brainstem nuclei thereby controlling motor behavior. A less well known fact is that the GPi also projects to the lateral habenula (LHb) which is often associated with the limbic system. Using the monkey performing a saccade task with positionally biased reward outcomes, we found that antidromically identified LHb-projecting neurons were distributed mainly in the dorsal and ventral bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
294
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(322 citation statements)
references
References 39 publications
26
294
1
1
Order By: Relevance
“…4I). The striosomes may, therefore, be the source of reward-related information that inhibits the habenula-projecting pallidal neurons in response to reward or reward prediction (5,14).…”
Section: Gph and Gpi/gpe Neurons Differ In Their Electrophysiologicalmentioning
confidence: 99%
See 2 more Smart Citations
“…4I). The striosomes may, therefore, be the source of reward-related information that inhibits the habenula-projecting pallidal neurons in response to reward or reward prediction (5,14).…”
Section: Gph and Gpi/gpe Neurons Differ In Their Electrophysiologicalmentioning
confidence: 99%
“…Recent in vivo recordings in primates have shown that the activity of these habenula-projecting pallidal neurons is modulated by the cues that predict the availability of reward (13,14) and not by aspects of movements. The majority of these pallidal neurons, as with lateral habenula neurons, are excited in response to errors in reward prediction or in expectation of an adverse outcome (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With these designs, we identified activations in posterior striatal regions, extending into the globus pallidus. The globus pallidus codes reward, receives inputs primarily from the ventral striatum, and sends rewardrelated information to the lateral habenula, which in turn innervates dopamine neurons (48,49). Critically, the distinction between striatal and lateral prefrontal responses suggests that not all expected value-sensitive regions integrate risk.…”
Section: Individual Differences In Risk Processingmentioning
confidence: 99%
“…Indeed, GAD67 is expressed in all subpallial regions in zebrafish (figure 1b) [5]. In particular, the entopeduncular nucleus (EN) has been identified as equivalent to the mammalian globus pallidus internal segment (GPi), which gives rise to the BG output to the thalamus and habenula [4,11]. In rodents, primates and humans, the dorsal striatum is essential for time keeping [12][13][14].…”
Section: Introductionmentioning
confidence: 99%